ORIGINALITY OF NOVELISTICHNOI TRADE OF VALERIAN PIDMOGYL’NY - Maftyn, N. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The peculiarity of modelling of the short stories architectonics in the works by V. Pidmohylny is investigated in the article. It has been shown the combination of features of the European short novel traditions in the author’s thinking as well as the influence of the philosophy of existentialism as the spiritual opposition to the occupation regime.